Distribution of CMV envelope glycoprotein B, H and N genotypes in infants with congenital cytomegalovirus symptomatic infection - Dong, Niuniu; Cao, Lingfeng; Zheng, Danni; Su, Liyun; Lu, Lijuan; Dong, Zuoquan; Xu, Menghua; Xu, Jin (Frontiers in Pediatrics, 2023)
Abstract Background: Cytomegalovirus (CMV) is the leading cause of congenital infections worldwide and contributes to long-term sequelae in neonates and children. CMV envelope glycoproteins play a vital role in virus entry and cell fusion. The association between CMV polymorphisms and clinical outcomes remains controversial. The present study aims to demonstrate the distribution of glycoprotein B (gB), H (gH) and N (gN) genotypes in congenitally CMV (cCMV) infected symptomatic infants and attempts to figure out the association between viral glycoprotein genotypes and clinical outcomes. Methods: Genotyping of gB, gH and gN was performed in 42 cCMV symptomatic infants and 149 infants with postnatal CMV (pCMV) infection in Children’s hospital of Fudan university. Nested PCR, gene sequencing and phylogenetic analyses were used to identify the genotypes. Results: Our study demonstrated that: 1. The CMV gB1, gH1 and gN1 were the predominant genotypes among symptomatic cCMV infected infants, while gB1, gH1 and gN3a were more prevalent in pCMV group. gH1 genotype has a significant association with symptomatic cCMV infection (p=0.006). 2. No significant correlation was found between CMV genotypes and hearing impairment. However, gH1 was more prevalent among cCMV infected infants with moderate/severe hearing loss although without statistical difference (p=0.130). 3. gB3 was more prevalent among infants with skin petechiae (p=0.049) and found to be associated with an increased risk of skin petechiae (OR=6.563). The gN4a subtype was significantly associated with chorioretinitis due to cCMV infection (p=0.007). 4. Urine viral loads were not significantly associated with different genotypes or hearing impairment among symptomatic cCMV infected infants. Conclusions: Our findings demonstrated the overall distribution of gB, gH and gN genotypes in infants with symptomatic cCMV infection in Shanghai for the first time. The findings in our study may suggest a possible association between gH1 genotype and early infancy hearing loss. gB3 genotype was associated with a 6.5-fold increased risk of petechiae while gN4a strongly correlated with chorioretinitis due to cCMV infection. No significant correlation was found between urine viral loads and CMV genotypes or hearing impairment in cCMV infected infants.